Application and Research Progress of Surface Engineering Technology in the Field of Plastic Machinery - ZHANG Peng, SU Xiao-lei, SHAN Lei (Cailiao Baohu)
According to the working conditions of plastic machinery and common failure modes, the principle and characteristics of key parts surface strengthening technology and its research status in improving comprehensive performance of parts were reviewed. Besides, it was pointed out that the composite technology of various types of surface strengthening method were the development direction to improve the plastic machinery and equipment surface quality and prolong the service life.